COOPERATION BETWEEN KAZAKHSTAN AND THE SHANGHAI COOPERATION ORGANIZATION AS A FACTOR IN THE DEVELOPMENT OF FOREIGN ECONOMIC ACTIVITY TODAY - NARIBAEV, Marat (CENTRAL ASIA AND THE CAUCASUS, 2009)
The Shanghai Cooperation Organization (SCO or Organization), which was created in order to strengthen regional security, enhance good-neighborly relations, and encourage multi-vector and multifaceted interaction among the member states, has become a major regional structure with broad opportunities for establishing mutually beneficial relations in the commercial and economic sphere. The immense territorial, human, raw material resource, and transport transit potential of the states participating in this Organization is an important factor of successful cooperation in this area. The SCO Secretariat and specialized economic institutions aim to promote cooperation in such vectors as foreign trade, investments, transportation and communications, energy, bank relations, agriculture, the environment, and the scientific-technical and social spheres. Within the SCO, Kazakhstan has succeeded in achieving results that are promoting the development of the foreign sector of its own economy and its gradual integration into the world economy. However, there are several problems and unresolved issues in the Organization’s activity that are hindering the development of foreign relations and putting the brakes on Kazakhstan’s foreign economic activity. Keeping in mind that the development of relations with the SCO meets the country’s interests and is extremely promising for its foreign economic activity, economic cooperation with the Organization must be strengthened.